Single components of complex chemical signals convey sex identity and individual variation. (May 2022) - Joshi, Mihir; Ellsworth, Brontë; Thaker, Maria
Abstract : Chemical signals, such as those used in social communication, are often present as complex blends of compounds, suggesting that complexity is important in signal perception. Very few studies, however, have examined the interactions between different components of complex signals in social signalling. In the Mysore day gecko, Cnemaspis mysoriensis, secretions of males are sufficient to elicit a behavioural response in females and these male secretions differ from those of females in the presence of two key chemical compounds: cholesterol and squalene. This provided us with an opportunity to determine the functions and interactions of individual components in a complex multicomponent chemical signal. First, using tongue flick assays, we established that both components independently elicit a behavioural response in females, but not males. When presented as a multicomponent mix, the response levels of females were similar to those shown towards the individual components, thereby indicating that cholesterol and squalene are redundant components. Moreover, female responses towards these components matched their level of response towards natural male secretions, confirming that both cholesterol and squalene signal sex identity of males. When presented with a gradient of multicomponent stimulus concentrations, females, but not males, incrementally adjusted their tongue flick responses to different levels. Further, responses of females were similar regardless of whether cholesterol or squalene was at a higher relative concentration in the multicomponent stimulus. These last two sets of results indicate that the overall concentration, but not the relative ratio of cholesterol and squalene, has the potential to encode information about male quality. Lack of responses by males to these compounds across experiments strongly indicate the role of cholesterol and squalene in intersexual, and not intrasexual, communication. Overall, we show that two sex-specific compounds in a complex multicomponent chemical signal are effective in communicating complex sexual information from males to conspecific females. Highlights: Chemical signals in males of Cnemaspis mysoriensis contain cholesterol and squalene. Only females respond to these compounds, in ways that indicate redundancy. Cholesterol and squalene are independently effective sex identity signals. Dose-dependent responses indicate potential for these to be mate assessment signals.